2014
DOI: 10.1039/c4ta00647j
|View full text |Cite
|
Sign up to set email alerts
|

A radar-like iron based nanohybrid as an efficient and stable electrocatalyst for oxygen reduction

Abstract: Iron phthalocyanine (FePc) coordinated with pyridyne cycloaddition of graphene sheets (PyNGs) as a high-performance electrocatalyst for ORR was fabricated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…MPc nanomaterials were found to have outstanding redox and electronic properties that were interesting in gas-sensors applications, active material for molecular electronic devices, photodetectors and photocatalytic catalyst [14][15][16][17][18]. It is found that the gas-sensor performance of MPc strongly depends on its microstructure [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…MPc nanomaterials were found to have outstanding redox and electronic properties that were interesting in gas-sensors applications, active material for molecular electronic devices, photodetectors and photocatalytic catalyst [14][15][16][17][18]. It is found that the gas-sensor performance of MPc strongly depends on its microstructure [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 68 ] Copyright 2014, Royal Society of Chemistry. c) Schematic illustrating synthesis of 3D FePc/AP–GA hybrids.…”
Section: Graphene/mmc‐based Orr Catalystsmentioning
confidence: 99%
“…[ 61–67 ] For example, Zhong et al. [ 68 ] synthesized a pyridine‐ligand‐functionalized graphene that reacted with iron phthalocyanine (FePc) to form a hybrid material ( Figure 3 a). They first used a mild and simple chemical reaction to modify the graphene and generate pyridine‐functionalized graphene (PyNG).…”
Section: Graphene/mmc‐based Orr Catalystsmentioning
confidence: 99%
“…Ibuprofen adsorption was recently demonstrated using fluorine‐functionalized bulk COF from ultrapure [208] and natural wastewater samples [209] . Furthermore, various new composites have been identified as effective adsorbents for the removal of diclofenac, [142,210,211] sulfonamides, [212] triclosan and triclocarban [213] from polluted water samples. COF‐based membranes have recently been incorporated into advanced water treatment as promising candidates for organic dye nanofiltration [166] .…”
Section: Applications Of Cof Compositesmentioning
confidence: 99%